Development of a portable optical strain sensor with applications to diagnostic testing of prestressed concrete - Zhao, Weixin (Kansas State University, 2011)
The current experimental method to determine the transfer length in prestressed concrete members consists of measuring concrete surface strains before and after de-tensioning with a mechanical strain gage. The method is prone to significant human errors and inaccuracies. In addition, since it is a time-consuming and tedious process, transfer lengths are seldom if ever measured on a production basis. A rapid, non-contact method for determining transfer lengths in prestressed concrete members has been developed. The new method utilizes laser-speckle patterns that are generated and digitally recorded at various points along the prestressed concrete member. User-friendly software incorporating robust and fast digital image processing algorithms was developed by the author to extract the surface strain information from the captured speckle patterns. Based on the laser speckle measurement technique, four (4) successively improved generations of designs have been made. A prototype was fabricated for each design either on an optical breadboard for concept validation, or in a portable self-contained unit for field testing. For each design, improvements were made based on the knowledge learned through the testing of the previous version prototype. The most recent generation prototype, incorporating a unique modular design concept and self-calibration function, has several preferable features. These include flexible adjustment of the gauge length, easy expansion to two-axis strain measurement, robustness and higher accuracy. Extensive testing has been conducted in the laboratory environment for validation of the sensor’s capability in concrete surface strain measurement. The experimental results from the laboratory testing have shown that the measurement precision of this new laser speckle strain measurement technique can easily achieve 20 microstrain. Comparison of the new sensor measurement results with those obtained using traditional strain gauges (Whittemore gauge and the electrical resistance strain gauge) showed excellent agreement. Furthermore, the laser speckle strain sensor was applied to transfer length measurement of typical prestressed concrete beams for both short term and long term monitoring. The measurement of transfer length by the sensor was unprecedented since it appears that it was the first time that laser speckle technique was applied to prestressed concrete inspection, and particularly for use in transfer length measurement. In the subsequent field application of the laser speckle strain sensor in a CXT railroad cross-tie plant, the technique reached 50 microstrain resolution, comparable to what could be obtained using mechanical gauge technology. It was also demonstrated that the technique was able to withstand extremely harsh manufacturing environments, making possible transfer length measurement on a production basis for the first time.
Keywords: Laser speckle; Prestressed concrete; Portable; Strain; Transfer length; Civil Engineering (0543); Mechanical Engineering (0548)